STUDI PENURUNAN KONSENTRASI SURFAKTAN DENGAN METODE PENGENDAPAN MENGGUNAKAN Ca(OH)2 - Azis Susanto (Purifikasi, 2003)
This research aim to settled high concentrated surfactants using calcium hydroxide. Using a jar test, the concentration of surfactants were measured. The batch test was started using a low concentration of surfactants at low pH. The results showed that calcium hydroxide was able to remove 95.16 % of surfactants. Which proved good performance of the chemical agent. This indicated that the chemical can be used to treat detergent rich content water or other effluent rich in surfactant content.